Serologic Status for Pandemic (H1N1) 2009 Virus, Taiwan - Huang, Daniel Tsung-Ning (Centers for Disease Control and Prevention, 2011)
We studied preexisting immunity to pandemic (H1N1) 2009 virus in persons in Taiwan. A total of 18 (36%) of 50 elderly adults in Taiwan born before 1935 had protective antibodies against currently circulating pandemic (H1N1) 2009 virus. Seasonal influenza vaccines induced antibodies that did not protect against pandemic (H1N1) 2009 virus.